Role of Artificial Intelligence Bots in Digital Marketing: A Cross-Sectional Study - Faiza Khurram (Business Review of Digital Revolution, 2023)
This research examines the influence of artificial intelligence (AI) bots on digital marketing, concentrating on content creation, poster creation, and competitor content analysis. The main goal was to determine how these AI-driven variables affected Japanese digital marketing managers’ tactics. A cross-sectional study was conducted on Japanese managers involved in digital marketing. The project examined AI Content Creation, Poster Creation, and Competitor Content Analysis. To determine how AI bots affect digital marketing, a poll was conducted. Study results show extensive usage of AI Content Creation, Poster Creation, and Competitor Content Analysis among Digital Marketing Managers. AI simplified content development, poster design, and rival strategy analysis, improving digital marketing performance. This research concludes that AI bots significantly impact digital marketing tactics for Japanese managers. AI Content Creation, AI Poster Creation, and AI Competitor Content Analysis have become essential to optimising digital marketing efforts, demonstrating AI’s transformational influence on digital marketing.
Keywords: AI Content Creation, AI Poster Creation, AI Competitor Content Analysis, AI Bots, Digital Marketing, Artificial Intelligence.